Determination of dynamic impact factor for continuous girder bridge due to vehicle braking force by finite element method and experimental - Toan, Nguyen Xuan; Duc, Tran Van (Vietnam Journal of Mechanics, 2017)
In this study, the finite element method (FEM) is used to investigate the dynamic response of continuous girder bridge due to moving three-axle vehicle . Vertical reaction forces of axles that change with time make bending vibration of girder significantly increase. The braking in the first span is able to create response in other spans. In addition, the dynamic impact factors are investigated by both FEM and experiment for Hoa Xuan bridge. The results of this study provide an improved understanding of the bridge dynamic behavior and can be used as additional references for bridge codes by practicing engineers.